Choledochal stenting for treatment of extrahepatic biliary obstruction in cats. (29th September 2021) - Griffin, Maureen A.; Culp, William T. N.; Giuffrida, Michelle A.; Selmic, Laura E.; Denitz, Jordan C.; Perry, James A.; Schoelkopf, Alexander C.; Milovancev, Milan; Phillips, Heidi; Wallace, Mandy L.; Steffey, Michele A.; Balsa, Ingrid M.; et al.
Abstract: Background: Limited information currently exists regarding the clinical progression and outcomes of cats that undergo choledochal stenting as a treatment for extrahepatic biliary obstruction (EHBO). Hypothesis/Objectives: Describe clinical characteristics, indications for choledochal stent placement, procedure, and outcomes in a cohort of cats undergoing choledochal stenting and evaluate risk factors associated with survival as well as recurrence of EHBO in affected cats. Animals: Twenty‐three client‐owned cats undergoing choledochal stent placement. Methods: Retrospective study. Medical records from 6 academic institutions were reviewed, and data were extracted and analyzed statistically. Results: Median age of cats was 10.1 years (range, 2‐16), and all cats had at least 2 clinical signs. Most common clinical signs were vomiting in 20/22 (90.9%), inappetence in 19/22 (86.4%), and lethargy in 19/23 (82.6%). Procedural complications were uncommon and rarely related to the stenting procedure. Clinical signs improved postoperatively in 15/20 (75.0%) cats and serum total bilirubin concentration decreased postoperatively in 13/19 (68.4%) cats. Eighteen (78.3%) cats survived to discharge. Recurrence of EHBO was documented in 7/18 (38.9%) cats that survived to discharge. Cholelithiasis was associated with recurrence of EHBO. Median survival time for cats that survived to discharge was 931 days (range, 19‐3034). Absence of peritoneal effusion was associated with survival to discharge. Conclusions and Clinical Importance: Choledochal stenting was an effective treatment modality in cats with EHBO with few procedural complications and potential for prolonged survival, but substantial risk for recurrence of EHBO was identified.